The effect of distribution channels and menu variations on increasing sales: A case of halal food - Indah Sahima Hsb; Kusmilawaty Kusmilawaty; Tri Inda Fadhila Rahma (LPMP Imperium, 2025)
This study aims to examine the impact of distribution channels and menu variety on sales growth in a halal food bread store. Utilizing an associative quantitative approach and a total sampling technique, 70 active resellers were selected as respondents. Data was collected through a questionnaire, and the results were analyzed using SPSS 25 with multiple linear regression. The findings of the study indicate that both menu variety and distribution methods significantly and positively influence sales growth to a certain extent. These results highlight the importance of integrated marketing strategies that combine expanding distribution and menu innovation to enhance competitiveness and foster business growth. This research is intended to serve as a reference for developing marketing strategies for small and medium-sized enterprises (SMEs) in the food sector. Public Interest Statement: This study is highly relevant for society, especially MSMEs in the food sector. Understanding the influence of distribution channels and menu variety on sales can help MSMEs optimise marketing strategies, improve efficiency and innovation, support local economic growth, enhance competitiveness, and provide consumers with more diverse and higher-quality products.